Leadership and fraud: A phenomenological study in Bengkulu provincial government - Suryani, Pesi; Gaol, Lasando Lumban (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to analyze the role of leadership in the prevention and detection of fraud in the Bengkulu Provincial GovernmentDesign/Methodology/Approach: The research method applied is a qualitative phenomenological approach, which allows for an in-depth exploration of subordinates' experiences and perceptions related to leadership and fraud. Data were collected through in-depth interviews, observations, and document analysis.Research findings: The findings indicate that transformational and transactional leadership styles play a significant role in fraud prevention. Leaders who adopt a transformational leadership style can enhance subordinates’ motivation and integrity through inspiration and idealized influence, while leaders with a transactional style focus on achieving targets through rewards and sanctions. The study also found that financial pressures, opportunities due to weaknesses in the internal control system, and rationalization of actions are the main factors driving fraud.Theoretical contribution/Originality: This research contributes to a holistic understanding of the interaction between leadership and fraud in the local government context and offers practical recommendations to improve the effectiveness of fraud prevention and detection through strengthening internal control systems, routine training, and adopting transformational leadership styles.Practitioner/Policy implication: The findings provide actionable insights for policymakers and practitioners in local government to strengthen fraud prevention efforts, which include enhancing leadership development programs, implementing stricter internal controls, and promoting ethical culture within the organizationResearch limitation/Implication: The study focuses on a single provincial government, which may limit the generalizability of the findings. Future research could be expanded to include multiple regions or sectors to provide broader insights into the relationship between leadership styles and fraud prevention.